2021
DOI: 10.1111/jam.15095
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted intervention of Bacillus spp. against salinity stress and Fusarium wilt in tomato

Abstract: Aim: This study aimed to screen halotolerant Bacillus strains able to promote growth and protect tomato plants against salt stress and Fusarium wilt (Fusarium oxysporum f. sp. lycopersici). Methods and Results: We evaluated some halotolerant strains of Bacillus spp. (Bacillus velezensis (AP-3) and Bacillus spp. (AP-6, AP-85 and AP-100)) to promote growth of tomato plants grown under salinity stress conditions and to protect them against Fusarium wilt disease. Such strains had been previously selected among 154… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…The ability of members of the B. subtilis -like group to biosynthesize specialized compounds with antimicrobial activity have made this species attractive for use as biocontrol agents ( Caulier et al., 2019 ; Penha et al., 2020 ). Thus, treatment of tomato seeds with antifungal B. velezensis AP3 ( Medeiros and Bettiol, 2021 ), B. subtilis MMS9 ( Patel and Saraf, 2017 ), and B. amyloliquefaciens FZB24 ( Elanchezhiyan et al., 2018 ) suppressed Fusarium wilt of the plant. In our study, the antifungal DD6, which contains biosynthetic gene clusters (BGC) associated with well-known antimicrobial secondary compounds, was unable to significantly decrease the development of symptoms of Fusarium wilt disease in tomato ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of members of the B. subtilis -like group to biosynthesize specialized compounds with antimicrobial activity have made this species attractive for use as biocontrol agents ( Caulier et al., 2019 ; Penha et al., 2020 ). Thus, treatment of tomato seeds with antifungal B. velezensis AP3 ( Medeiros and Bettiol, 2021 ), B. subtilis MMS9 ( Patel and Saraf, 2017 ), and B. amyloliquefaciens FZB24 ( Elanchezhiyan et al., 2018 ) suppressed Fusarium wilt of the plant. In our study, the antifungal DD6, which contains biosynthetic gene clusters (BGC) associated with well-known antimicrobial secondary compounds, was unable to significantly decrease the development of symptoms of Fusarium wilt disease in tomato ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, biological control of Fusarium wilt of tomato has attracted considerable attention ( La Torre et al., 2016 ; Sallam et al., 2019 ; de Lamo and Takken, 2020 ; Doan et al., 2020 ; Vinchira-Villarraga et al., 2021 ). Several species of the bacterial genus Bacillus have proved to be promising biocontrol agents, since they protect through several modes of action, such as competition, parasitism, antibiosis, and induced resistance ( Akram et al., 2016 ; Elanchezhiyan et al., 2018 ; Bhattacharya et al., 2019 ; Medeiros and Bettiol, 2021 ; Zhang et al., 2021 ). For the latter mechanism, some Bacillus species can activate immediate defense responses, predisposing the plant to react faster and stronger to subsequent pathogen attack, a mechanism known as defense priming ( Tonelli and Fabra, 2014 ; Wang et al., 2014 ; Mauch-Mani et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bacillus strain QST-713 (Serenade TM ) promotes the growth of tomato plants and protects them from salt stress and Fusarium oxysporum f. sp. lycopersici attack (Medeiros and Bettiol, 2021 ). In greenhouse and field experiments, the application of the commercial biocontrol treatment Stargus (with the active ingredient B. amyloliquefaciens F727) was effective in controlling the severity of crown and root rot induced by Phytopythium vexans infesting ginkgo and red maple plants (Panth et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study of PGPR, mainly including Mesorhizobium and Allorhizobium, intracellular PGPR, and Bacillus, Pseudomonas and Azotobacter extracellular PGPR (Li et al, 2020), has attracted the attention of scholars at home and abroad. To screen salt-tolerant Bacillus strains and growth-promoting microorganisms, Medeiros and Bettiol (2021) evaluated: the production of iron carriers and indoleacetic acid (IAA) and solubilization of phosphate. A study found that SDTB038 could produce indole acetic acid.…”
Section: Discussionmentioning
confidence: 99%